Historical trend in harbour seal (Phoca vitulina) abundance in Iceland back to the year 1912 - Hauksson, Erlingur; Einarsson, Sólmundur T (NAMMCO Scientific Publications, 2010)
The harbour seal (Phoca vitulina) is Iceland’s most abundant seal and has likely been exploited since the settlement of the country. Detailed information on skin exports is available as far back as 1912, and suggests that the catch, consisting mainly of pups, was far higher in the early 20th century than now. Assuming that skin exports were proportional to catches, these data were used to back-calculate the size of the Icelandic harbour seal population to the year 1912. The results indicate that the harbour seal population was considerably larger in the early 19th century than at present, about 60,000 (90% CI:40-100) animals. Aerial surveys conducted since 1980 indicate that the population has declined from 33,000 (90% CI:26,000-44,000) animals in 1980 to about 12,000 (90% CI:9,000-16,000) animals in 2006. The population time series suggests thatthe stock began to decline rapidly around 1960 and continued to decrease until 2003. In the period 1980 - 2003, the population declined even though reported catches were relatively low. Harvest rate had probably been about 10% before 1960. Between 1960 and 1980 the reported harvest rate increased to about 13%, but unknown numbers of adult seals were also taken as by-catch and shot in defence of salmon rivers. Since 2003, total removals have decreased and the population decline appears to have ceased. Entanglements in fishing gear and other incidental unreported hunting could increase again in the future. Therefore, the population must be monitored on a regular basis, and better information on by-catch and other unreported harvest is needed.